The Rhino Early Iron Age site, Thabazimbi, South Africa. Issue 3 (2nd July 2020) - Huffman, Thomas N.; Whitelaw, Gavin; Tarduno, John A.; Watkeys, Michael K.; Woodborne, Stephan
ABSTRACT: The Rhino Early Iron Age site near Thabazimbi in the far north of South Africa is a sixth- to eighth-century AD example of an agricultural settlement that followed the principles of the Central Cattle Pattern. In addition to settlement features, salvage excavations yielded a fragment of a 'Lydenburg Head' in association with Happy Rest pottery. Together with other data, head sculptures appear to be a Kalundu Tradition trait. The head, long-term occupation and settlement extent show that Rhino was a chief's headquarters. The Happy Rest assemblage provides an example of interaction with different Bantu-speaking people in the region who made Mzonjani pottery, while Later Stone Age scrapers attest to interaction with hunter-gatherers. Magnetic measurements led to a re-evaluation of archaeological interpretations of the site and show the mutual benefit of the joint study.